The Development of Marketing Strategy of Community Enterprise in Sa Kaeo Province - et. al., Pattarapon Chummee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research had the following objectives: 1) To study the general characteristics and levels of importance of community enterprise in Sa Kaeo Province 2) To study components for community enterprise development 3) To develop marketing strategies for community enterprise and 4) To evaluate marketing strategies for community enterprise. The target population was 337 community enterprise’s entrepreneurs in Sa Kaeo Province. Composition analysis was used to group the variables and test for accuracy and conduct a qualitative study to analyze and evaluate SWOT and then developed a marketing strategy including evaluating the marketing strategy in the next step. The findings were as follows: The general characterization of the surveyed community enterprises showed that the total 337 respondents, with the majority of respondents being female. Most of the respondents were aged 31-35 years and had an education level lower than a bachelor's degree. It was found that the majority of respondents had 5-10 years of experience in community enterprise entrepreneurship. Among the total of the samples, most respondents had the type of product or service which showed the largest number of fabric products. For the results of the analysis of the level of importance from the opinions of the community enterprise entrepreneurs in Sa Kaeo Province, it was found that community enterprise entrepreneurs had opinions on marketing mix factors at a high level overall Including products and services, price, service location, distribution channel, promotion, personal marketing, physical aspects and processes. The results of the synthesis of the development of community enterprise marketing strategies in Sa Kaeo Province. A proactive strategy was to create a unique product. A modified strategy was to increase distribution channels. Preventive strategies included promoting education and passive strategies such as relationship building